1998
DOI: 10.1080/10408699891274237
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Muscle Proteases and Lipases in Flavor Development During the Processing of Dry-Cured Ham

Abstract: The processing of dry-cured ham is very complex and involves numerous biochemical reactions that are reviewed in this article. Muscle proteins undergo an intense proteolysis, resulting in a great number of small peptides and high amounts of free amino acids. The enzymes responsible of these changes are proteinases (cathepsins B, D, H, and L and, to a less extent, calpains) and exopeptidases (peptidases and aminopeptidases). Muscle and adipose tissue lipids are also subject to intense lipolysis, generating free… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
220
1
10

Year Published

1999
1999
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 413 publications
(246 citation statements)
references
References 63 publications
7
220
1
10
Order By: Relevance
“…Fermented soybean products especially those prepared by the fungus R. oligosporus, are rich in oleic and linoleic fatty acids. Many previous studies have shown that fatty acid contents play an important role in the flavor of the food products (Larick, Turner, 1990;Ha, Lindsay, 1991;Toldra, Flores 1998). Soybeans in particular are known to contain fair amounts of lipids, and in general are considered 'undesirable' by most consumers in the western countries.…”
Section: Resultsmentioning
confidence: 99%
“…Fermented soybean products especially those prepared by the fungus R. oligosporus, are rich in oleic and linoleic fatty acids. Many previous studies have shown that fatty acid contents play an important role in the flavor of the food products (Larick, Turner, 1990;Ha, Lindsay, 1991;Toldra, Flores 1998). Soybeans in particular are known to contain fair amounts of lipids, and in general are considered 'undesirable' by most consumers in the western countries.…”
Section: Resultsmentioning
confidence: 99%
“…Similar results was found by Ruiz et al [10] in dry cured Iberian ham. Temperature can also affect enzyme activities and lead to the different release rates of oligopeptide and free amino acids [11]. Zhao et al [12] found that there was a significant interactive effect on cathepsin B and L activity with temperature and salt content (P < 0.001).…”
Section: Oligopeptides and Free Amino Acidsmentioning
confidence: 99%
“…The umami taste, which is described as savory, brothy or beefy, comes mainly from the free amino acids, oligopeptides as well as from certain 5'-ribonucleotides such as inosine-5'-monophosphate (IMP) [8]. In addition, those umami tastes related chemical compounds are also influenced by curing time [9,10], curing agent usage as well as temperature [11,12], and they are precursors for the formation of volatile odor-active compounds through Strecker degradation and Maillard reactions [13,14]. In spite of the increasing demand for duck meat products day by day [2], little information is available about the contribution of each Chinese traditional processing stage to the final duck breast meat products.…”
mentioning
confidence: 99%
“…Thus, lipase was utilized for the enhancement of the flavour quality (Toldra and Flores, 1998). Lipase catalyzed interesterification under the controlled condition was adapted to enrich the naturally occurring oils and fats which lacked well balanced fatty acids.…”
Section: Food Industry Applicationsmentioning
confidence: 99%